Activities of OECD in 1971; : report by the Secretary General - OECD; Organisation for Economic Co-operation and Development (Paris: Organisation for Economic Co-operation and Development, 1972)
This is to achieve the highest sustainable economic growth and employment, sound economic expansion ansd expansion of the world trade.
aia 21/03/2019
Loans
Keywords: International trade; Agriculture; Industries